Psychological support and outcomes for ICU patients - Papathanassoglou, Elizabeth (My University, 2010)
AIMS AND OBJECTIVES: To critically review evidence on the effects of psychological support during intensive care unit (ICU) treatment on adult ICU patients' psychological and physiological outcomes. Evidence from intervention studies on imagery and relaxation has been included, as well. BACKGROUND: Stress and negative emotions may have both immediate, as well as long-term effects on ICU patients' psychological and physical well-being, and they are linked to delayed physical recovery. DESIGN, METHODS: A narrative critical review methodology was employed. Databases searched included Medline, CINAHL, PubMed, PsychInfo and the Cochrane Library. Experimental, quasi-experimental or pretest-posttest peer-reviewed intervention studies published since 1970 were included. RESULTS: Fourteen studies: seven on nurse led relaxation, three on guided imagery, one on nurse-patient interaction, two on physician-patient interaction and one correlational study on perceived social support were included. The results suggest significant improvements in patients' outcomes: improved vital signs, decrease in pain ratings, anxiety, rate of complications and length of stay, and improved sleep and patient satisfaction. Eight studies employed randomized experimental, four quasi-experimental and two descriptive correlational designs. Two studies explored effects on patients' sleep, and two on procedure-related pain. Conclusions: The literature is limited in exploring the effects of nurse-patient interactions. The amount and quality of psychosocial support in the ICU, as well as imagery and relaxation techniques, are linked to short-term and long-term patients' outcomes. RELEVANCE TO CLINICAL PRACTICE: ICU nurses need to engage in psychological support in a systematic way, and to acknowledge the high priority of support interventions
Keywords: Critical care nursing; Stress (psychology); Intensive care nursing; Patients; Nurses; Psychotherapy